Development of Generator Set Product Services Using Quality Function Deployment at PT X - Neysa Ivah Umma; Yitno Utomo (TALENTA Publisher, 2023)
Â In the service industry, service quality has a significant effect on customer satisfaction. The manufacturing industry and the service industry have different characters, as well as the measurement of the quality of the services produced. The company's ignorance of customer desires and expectations of the services provided causes services far from the expectations desired by the company which can result in moving consumers to competitors who will provide services in accordance with their expectations. Therefore, this research was conducted with the aim of developing services in generator rental using Quality Function Deployment (QFD) method with the hope of providing an overview of the desires and expectations desired by consumers for services owned by PT X. The results of the Quality Function Deployment analysis of the highest scale factor value in the analysis using the QFD method the top order is on the characteristics of